2010
DOI: 10.5851/kosfa.2010.30.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Quality Characteristics between Commercial Korean Native Chickens and Broilers

Abstract: To investigate the differences in the quality characteristics between commercial Korean native chicken (KNC) and broiler (CB), nutritive and quality parameters of the two chicken species were determined. The KNC thigh muscle had a lower content of crude fat and higher crude ash than the CB thigh. In regards to the fatty acid composition, KNC breast muscle had a higher content of arachidonic acid (C20:4) than CB. The level of inosine was higher in the CB thigh muscle than KNC but there was little difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
63
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 14 publications
10
63
1
7
Order By: Relevance
“…Additionally, Kiyohara et al showed that total taste intensity and aftertaste of both chicken soup and steamed minced meat were significantly greater when Hinai-jidori chickens were fed an arachidonic acidenriched diet. Choe et al (2010) observed comparable linoleic acid contents between the KNC and CB meats. However, the lipid layer of soup made with CB had a significantly lower content of linoleic acid than that of KNC (Table 3).…”
Section: Fatty Acid Composition Of Lipid Layers Separated From Soupsmentioning
confidence: 58%
“…Additionally, Kiyohara et al showed that total taste intensity and aftertaste of both chicken soup and steamed minced meat were significantly greater when Hinai-jidori chickens were fed an arachidonic acidenriched diet. Choe et al (2010) observed comparable linoleic acid contents between the KNC and CB meats. However, the lipid layer of soup made with CB had a significantly lower content of linoleic acid than that of KNC (Table 3).…”
Section: Fatty Acid Composition Of Lipid Layers Separated From Soupsmentioning
confidence: 58%
“…실제로 국내에서 의 닭 사육수는 2016년 6월 기준 약 18,070만 수로 2006년 12월 기준 11,918만 수와 비교하여 약 51.6%의 증가치를 보 였다 (통계청, 2016). 이중에서도 일반적으로 이용하는 닭인 브로일러종은 근육생성능력이 뛰어나고 성장률이 높아 5∼6 주령 수준에서도 시장에서 판매된다 (Choe et al, 2010). 반 면, 최소 60주령 이후부터 산란율이 떨어져 도태되는 산란 성계육은 다즙성이 적고 조직감이 질기기 때문에 식품으로 써 추가 활용하기에 어려움이 있다 (Abdalla et al, 2012).…”
Section: 서 론unclassified
“…No scientific literature was found regarding the factors affecting the availability of these bioactive compounds in KNCs and CBs, except that of Jung et al (2013). Although meat quality characteristics of KNCs and CBs were compared previously (Choe et al, 2010;Jayasena et al, 2013), comparisons of these bioactive compounds in these two breeds are still unavailable. Therefore, the present study was primarily designed to compare the carnosine, anserine, betaine and carnitine contents of breast and leg meat from KNCs and CBs at their respective market ages and to determine the changes in these compounds during the cooking process.…”
mentioning
confidence: 95%